Smoking and All-cause Mortality in Older Adults - Müezzinler, Aysel; Mons, Ute; Gellert, Carolin; Schöttker, Ben; Jansen, Eugène; Kee, Frank; O’Doherty, Mark G.; Kuulasmaa, Kari; Freedman, Neal D.; Abnet, Christian C.; Wolk, Alicja; Håkansson, Niclas; et al. (American Journal of Preventive Medicine)

Healthy aging through a healthy diet : never too old to eat healthy?! - Jankovic, Nicole

Adherence to the Dutch dietary guidelines is inversely associated with 20-year mortality in a large prospective cohort study - van Lee, L; Geelen, A; Kiefte-de Jong, J C; Witteman, J C M; Hofman, A; Vonk, N; Jankovic, N; Hooft van Huysduynen, E J C; de Vries, J H M; van 't Veer, P; Franco, O H; Feskens, E J M (European Journal of Clinical Nutrition)

Die Rückforderung unzulässiger Bearbeitungsentgelte im Spannungsfeld von Rechtsfrieden und Verbraucherschutz - Bartlitz, David (Zeitschrift für Bank- und Kapitalmarktrecht (BKR))

Life is live. Experiencing Music in the digital Age - Flath, Beate (International Journal of Music Business Research)

Groove - Kultur - Unterricht. Studien zur pädagogischen Erschließung einer musikkulturellen Praktik.
»Groove« bezeichnet eine rhythmische Qualität populärer Musik. Dem multidimensionalen Groove-Phänomen als zentralem Element alltäglicher Musikrezeption standen bislang disparate wissenschaftliche Erklärungsansätze gegenüber, ohne den für die Pädagogik nötigen Überblick zu ermöglichen. Heinrich Klingmann liefert erstmals eine profunde, transdisziplinäre Analyse des Grooves als Gegenstand der Rhythmusforschung, Musikethnologie, Kulturwissenschaft und Pädagogik. Auf dieser Grundlage entwirft er eine »Kontextkritische Musikdidaktik«, die es erlaubt, das Bildungspotential populärer Musik zu erschließen, ohne ihre Eigengesetzlichkeit zu vernachlässigen.

(Pop-)Musik-Didaktik für freie Menschen. Pluralismus und Transkulturalität als Herausforderungen für die Musikpädagogik. - Klingmann, Heinrich (Popmusik-Vermittlung. Zwischen Schule, Universität und Beruf.)

Percussionsklasse. Inklusive Begründungen. - Klingmann, Heinrich (Musikunterricht 2, Sammelband zum Bundeskongres Musikunterricht in Leipzig 2014)

Historical Thinking, Competencies and their Measurement: Theoretical Challenges and Testing Concepts - Meyer-Hamme, Johannes; Körber, Andreas (New Directions in Assessing Historical Thinking)

Lernaufgaben im inklusiven Sprachunterricht. - Uhl, Benjamin; Topalović, Elvira (Inklusive Deutschdidaktik. Grundschulunterricht)

Grammatik bewusst machen.

Wirksamkeit von Bearbeitungsentgelten in Darlehensverträgen mit Unternehmern. Anmerkung zu LG Kleve, Urt. v. 18.08.2015 - 4 O 13/15 - Bartlitz, David (Entscheidungen zum Wirtschaftsrecht (EWiR))

Michael Fischer: Religion, Nation, Krieg. Der Lutherchoral "Eine feste Burg ist unser Gott" zwischen Befreiungskriegen und Erstem Weltkrieg, Waxmann-Verlag, Münster 2014 - Janus, Richard (Jahrbuch zur Westfälischen Kirchengeschichte)

Online Tests for Evaluating Learning Success - Hesse, Kerstin (Extended Abstract der khdm Conference 2015, 8 Seiten. (Dieser Extended Abstract ist online publiziert als khdm-Report zur khdm Conference 2015.))

Religiosität und Literatur in Novalis’ "Heinrich von Ofterdingen" und Orhan Pamuks "Das Neue Leben". Eine Studie der interkulturellen Germanistik - Schulte Eickholt, Swen

Exploring the Space of Topic Coherence Measures - Röder, Michael; Both, Andreas; Hinneburg, Alexander (Proceedings of the eight International Conference on Web Search and Data Mining, Shanghai, February 2-6)
Keywords: group_aksw SIMBA sys:relevantFor:infai sys:relevantFor:bis roeder palmetto

The Contingent Role of Centrality in IT Network Governance: An Empirical Examination - Trang, Simon Thanh-Nam; Zander, S.; Kolbe, L. M. (Pacific Asian Journal of the Association for Information Systems)

VCCFinder: Finding Potential Vulnerabilities in Open-Source Projects to Assist Code Audits - Perl, Henning; Dechand, Sergej; Smith, Matthew; Arp, Daniel; Yamaguchi, Fabian; Rieck, Konrad; Fahl, Sascha; Acar, Yasemin (Proceedings of the 22nd ACM SIGSAC Conference on Computer and Communications Security)

To Pin or Not to Pin-Helping App Developers Bullet Proof Their TLS Connections - Oltrogge, Marten; Acar, Yasemin; Dechand, Sergej; Smith, Matthew; Fahl, Sascha (24th USENIX Security Symposium, USENIX Security 15, Washington, D.C., USA, August 12-14, 2015)

Evaluation of a Multi-Objective EA on Benchmark Instances for Dynamic Routing of a Vehicle - Meisel, Stephan; Grimme, Christian; Bossek, Jakob; Wölck, Martin; Rudolph, Guenter; Trautmann, Heike (Proceedings of the Genetic and Evolutionary Computation Conference (GECCO ’15))
We evaluate the performance of a multi-objective evolutionary algorithm on a class of dynamic routing problems with a single vehicle. In particular we focus on relating algorithmic performance to the most prominent characteristics of problem instances. The routing problem considers two types of customers: mandatory customers must be visited whereas optional customers do not necessarily have to be visited. Moreover, mandatory customers are known prior to the start of the tour whereas optional customers request for service at later points in time with the vehicle already being on its way. The multi-objective optimization problem then results as maximizing the number of visited customers while simultaneously minimizing total travel time. As an a-posteriori evaluation tool, the evolutionary algorithm aims at approximating the related Pareto set for specifically designed benchmarking instances differing in terms of number of customers, geographical layout, fraction of mandatory customers, and request times of optional customers. Conceptional and experimental comparisons to online heuristic procedures are provided.